Pengaruh Efikasi Diri terhadap Self-Regulated Learning - Salsabylla, Waode Naifa Claresta; Ahmad; Jalal, Novita Maulidya (Institut Agama Islam Negeri Parepare, 2023)
Changes in the learning process and environment can make it difficult for students to adapt to new ways of learning. Students who are able to self-regulated learning can plan, supervise, and evaluate various aspects related to the learning process. One of the factors that influence self-regulated learning is self-efficacy. Self-efficacy is a belief in their ability to perform certain tasks. This study aims to determine the effect of self-efficacy on self-regulated learning. This study used a quantitative method using a measuring instrument in the form of a self-regulated learning scale and a self-efficacy scale. Test the hypothesis in this study using a simple regression analysis. The results of the analysis show a significance value of 0.000 <0.05, so it can be concluded that there is a significant influence between self-efficacy on self-regulated learning. The value of the coefficient of determination is 0.392, so it can be concluded that self-efficacy has an effect of 39.2% on self-regulated learning, where 60.8% is influenced by other variables that the researchers did not examine. Implication of this research in the field of educational psychology in providing a deeper understanding of the effect of self-efficacy on self-regulated learning in changing learning situations